The Occurrence of Asthenopia among Online Gamers in Kupang City, East Nusa Tenggara - Anggie Elzha Yulindri Welkis; Noorce Christin Berek; Agus Setyobudi (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Data from WHO shows that asthenopia cases in the world range from 75-90%. Astenopia can result from excessive efforts of the vision system to obtain the quality of vision it should. Excessive online gaming habits have the potential to result in decreased vision quality. This problem needs to be considered because asthenopia is an early symptom sign of more serious visual impairment. This study aimed to discover an overview of the incidence of asthenopia among online game players in Kupang City based on the duration, distance of smartphones, body position, and eye rest while playing online games. Subjects and Method: It was a descriptive study conducted in Kupang City from March to April 2023. With a total of 378 online game players aged 15-24 years selected by purposive sampling. The dependent variable was the incidence of asthenopia. The independent variables were the duration of playing online games, the viewing distance of smartphone, body position, and eye rest. The data collection techniques used was questionnaires. The data were presented descriptively. Results: A total of 367 people (97.1%) complained about symptoms of eyestrain (asthenopia), 251 people (66.4%) played online games with a duration of >2 hours and other 127 people (33.6%) played online games <2 hours. 277 people (73.3%) used smartphones with a distance of <30 cm and other 101 people (26.7%) with a distance of >30 cm. 184 people (48.7%) played online games while lying down and 194 people (51.3%) sitting. 187 people (49.5%) did not do eye rest and as many as 191 people (50.5%) did eye rest consisting of 53 people (14.0%) doing micro break, 55 people (14.6%) doing mini break and 83 people (22.0%) doing maxi break. Conclusion: Different types of asthenopia have been discovered. The most common incidence of asthenopia is experienced by online game players with risky viewing distance of smartphone.